The Effectiveness of Social Media Content Creators in Increasing MSME Sales in Sodong Hilir District - Okta, Setyo Luthfi; Saefullah, Rifki (International Journal of Linguistics, Communication, and Broadcasting, 2025)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize social media as a marketing tool. One emerging digital marketing strategy is the use of social media content creators, who produce review-based content that can influence consumer perceptions and purchasing decisions. However, the effectiveness of content creator reviews in increasing MSME sales, particularly at the sub-district level, remains unclear. In Sodong Hilir District, Tasikmalaya Regency, many MSMEs have received independent reviews from social media content creators. Despite increased exposure, the impact of these reviews on sales performance has not been consistently significant. Therefore, this study aims to analyze the effectiveness of social media content creators in increasing MSME sales in Sodong Hilir District and to identify the impacts perceived by MSME owners. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews with ten MSME owners, observations of social media promotional activities, and documentation of content creator review interactions. The data were analyzed using qualitative interactive analysis, including data reduction, data presentation, and conclusion drawing. The results indicate that independent reviews by social media content creators positively influence MSME visibility, audience engagement, and brand awareness. While several MSMEs experienced a temporary increase in customer visits and sales after the reviews were published, the impact on sales was not consistently sustained. Overall, social media content creators were found to be more effective in enhancing brand awareness and consumer trust than in generating immediate and long-term sales growth.